X-Ray Diffraction and Microstructure of Tin Dioxide with Addition of Fe - Posman Manurung (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2011)
Preparation and characterization of tin dioxide, SnO2, had been carried out by precipitation process of SnCl2.2H2O in ammonia and aqua solutions with comparison of 1 : 7. FeCl3 was added to solution with variation of 0, 0,1, 0.2, 0.5 and 1.0 gram respectively and then sintered at 900°C. The X-ray diffraction (XRD) analysis shows that the intensity of diffraction increases with the addition of Fe. The addition of Fe does not cause the new phase. Generally, the Bragg angle is relative same for all samples that means Fe does not change significantly the cell parameters. Scanning electron microscopy (SEM) image shows the microstructure changed with the addition of Fe. On the small addition, the microstructure tends to oval and on the larger addition to plateau.